2004
DOI: 10.1271/bbb.68.175
|View full text |Cite
|
Sign up to set email alerts
|

Frost-susceptible Protein in Plasma Membranes in Tubers ofHelianthus tuberosusL.

Abstract: When plasma membranes were prepared from tubers of Helianthus tuberosus L. (Jerusalem artichoke) frozen at a sublethal temperature (À10 C), the levels of some plasma membrane proteins, named frost-susceptible proteins (FSPs), decreased [Uemura, M., et al., Plant Physiol., 80, 187-195 (1986)]. The aim of this study was to characterize the response of FSP120, which is named FSP-3 in a previous report, to freezing treatment by immunoblotting. Levels of FSP120 in the plasma membranes of tubers decreased after sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The amount of FSP120 in the crude extract of frozen tubers remained at a comparable level to that of the unfrozen tubers. These results suggest that FSP120 might be released from plasma membranes during freezing treatment of H. tuberosus tubers (21). Kocsis et al (22) examining the response of inulin obtained from JA to frosts, found that its late varieties (e.g.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The amount of FSP120 in the crude extract of frozen tubers remained at a comparable level to that of the unfrozen tubers. These results suggest that FSP120 might be released from plasma membranes during freezing treatment of H. tuberosus tubers (21). Kocsis et al (22) examining the response of inulin obtained from JA to frosts, found that its late varieties (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Dormancy reduces the H. tuberosus population in such climate to a single growth cycle per year (13)(14)20). Arakawa et al (21) were characterised the responses of FSP120, also known as FSP-3, to freezing treatment by immunoblotting. Levels of FSP120 in the plasma membranes of tubers decreased after sublethal freezing, whereas no degraded products were detected in the microsomes or the soluble fraction.…”
Section: Introductionmentioning
confidence: 99%